The mineral assemblege andalusite-corundum from "La Aurora" pegmatite from Mazán Pegmatitic Field, Northwestern Argentina - Sardi, Fernando Guillermo (2009)
It is the fi rst mention of the andalusite-corundum paragenesis in the pegmatites from the Mazán pegmatitic fi eld of the Pampean Pegmatitic Province. This paragenesis has been found into the K-feldspar zone of the "La Aurora" pegmatite, which has spatial relationship with the strongly peraluminous Mazán Granite. The genetic studies on the pegmatite are preliminary, but according to the literature data, "La Aurora" pegmatite could have been formed from supracortical H2O-saturated peraluminous melts. The cell parameters (in Å) of andalusite and corundum were determined by means of XRD. The mean value determined for andalusite are ao = 7,794; bo = 7,897; co = 5,554 and for corundum ao = 4,754; co = 12,993.